A Natural Experiment on Sick Pay Cuts, Sickness Absence, and Labor Costs - Nicolas R. Ziebarth; Martin Karlsson (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This study estimates the reform effects of a reduction in statutory sick pay levels on various outcome dimensions. A federal law reduced the legal obligation of German employers to provide 100 percent continued wages for up to six weeks per sickness episode to 80 percent. This measure increased the ratio of employees having no days of absence by about 7.5 percent. The mean number of absence days per year decreased by about 5 percent. The reform might have reduced total labor costs by about exteuro1.5 billion per year which might have led to the creation of around 50,000 new jobs.
Keywords: H51; I18; J22; 330